2013
DOI: 10.1016/j.jdiacomp.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot ulcer incidence in relation to plantar pressure magnitude and measurement location

Abstract: Aims We prospectively examined the relationship between site-specific peak plantar pressure (PPP) and ulcer risk. Researchers have previously reported associations between diabetic foot ulcer and elevated plantar foot pressure, but the effect of location-specific pressures has not been studied. Methods Diabetic subjects (n = 591) were enrolled from a single VA hospital. Five measurements of in-shoe plantar pressure were collected using F-Scan. Pressures were measured at 8 areas: heel, lateral midfoot, medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 24 publications
2
86
1
1
Order By: Relevance
“…This finding could be one possible explanation for the fact that increases in peak plantar pressure 10 , associated with other factors, precede the appearance of ulcerations and foot amputations in this population 20,21 consistent with the findings of this study, which indicated that points receiving abusive overload to structures frequently bore signs of existing injuries.…”
Section: Discussionsupporting
confidence: 90%
“…This finding could be one possible explanation for the fact that increases in peak plantar pressure 10 , associated with other factors, precede the appearance of ulcerations and foot amputations in this population 20,21 consistent with the findings of this study, which indicated that points receiving abusive overload to structures frequently bore signs of existing injuries.…”
Section: Discussionsupporting
confidence: 90%
“…The low sensitivity and specificity values reported by these studies indicate that feet with high pressure values may not ulcerate, while feet with "normal" pressures could ulcerate. A more recent study (Ledoux et al, 2013) enhanced the previous findings by indicating significantly greater peak plantar pressure values for ulcers occurring at the metatarsal heads, which hosted only 25% of the wounds. Additionally, a prospective study by Veves et al (1992) investigated ulcer development at peak pressure locations but only found matches in 38% of participants.…”
Section: Introductionmentioning
confidence: 48%
“…During daily life, the corneodesmosomes, the corneocyte keratin network, the desmosomes, the collagen and elastin fibers, the adsorbed ground substance and the fibrous walls withstood easily these combined stresses. Unfortunately cases happen for which existing histopathological events (localized light or severe ischemia [39][40][41], bridges already jeopardized by previous damaging mechanical loads [42][43][44][45], impaired lymphatic drainage and interstitial fluid flows [46][47][48], reperfusion injuries [49][50]) may have weakened their strength. In such cases, when soft tissues are already jeopardized, their degradation will continue and increase [6].…”
Section: Layer-materials Point Levelmentioning
confidence: 99%